Durability assessment of mechanochemically activated geopolymer concrete with a low molarity alkali solution - Ashita Singh; Sudhir Singh Bhadauria; Akshay Anil Thakare; Anil Kumar; Manish Mudgal; Sandeep Chaudhary (Case Studies in Construction Materials, 2024)
The prevailing practices of geopolymer concrete (GC) preparation use a high concentration of alkali activators, which is uneconomical. It is imperative to develop GC of low-concentration activators with enhanced durability for field implementation. Mechanochemical activation of geopolymer increases the reactivity of its raw materials by converting the crystalline phase to an amorphous phase. It has been illustrated in the present study that mechanochemical activation aids in achieving GC of desired properties at low concentrations of alkali activators. The mechanochemical activation of ground granulated blast furnace slag (GGBS) with sodium metasilicate was carried out to prepare GC of low (2 M) and high (12 M) alkali concentrations. The Portland slag cement-based concrete (PC) was cast to compare the durability performance of GC. The durability of the three concrete mixes was examined in terms of water absorption, the volume of permeable voids (VPV), water and chloride permeability, homogeneity, and acid resistance. The microstructural characterization of concrete samples exposed to acid were carried out by X-ray diffraction, field emission scanning electron microscope, and energy dispersive X-ray spectrometer. The results indicated that GC with a low concentration of activator exhibited lesser water absorption, VPV, and permeability, whereas it offered higher resistance to acids and chloride ion penetrability. Low-concentration GC had a dense and compact structure due to the coexistence of geopolymeric and hydration products, leading to better performance than high-concentration GC and PC. The evaluation of cost and carbon emission of PC, and GC mixes suggests GC as a sustainable alternative to traditional concrete. Although PC is economically viable, the study suggest use of GC with low alkali concentration due to its environmental benefits with a minor increase in cost.